2015
DOI: 10.1111/imm.12371
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of Mycobacterium tuberculosis‐infected monocytes reveals IL26 as a new candidate gene for tuberculosis susceptibility

Abstract: Summary Differences in the activity of monocytes/macrophages, important target cells of Mycobacterium tuberculosis, might influence tuberculosis progression. With the purpose of identifying candidate genes for tuberculosis susceptibility we infected monocytes from both healthy elderly individuals (a tuberculosis susceptibility group) and elderly tuberculosis patients with M. tuberculosis, and performed a microarray experiment. We detected 78 differentially expressed transcripts and confirmed these results by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
0
21
1
Order By: Relevance
“…Lazar-Molnar et al 60 Barber et al 61 Fujita K et al 62 Sakai et al 63 Th1 cytokines and TB G Zeng et al Guerra-Laso et al 64 Che et al 65 Wareham et al 66 IL-7/15 ELISA, cytometric bead assay Enhanced Mtb survival was shown in IL-7-or IL-15-treated mice.…”
Section: Pd-1 Real-time Pcr Flow Cytometrymentioning
confidence: 99%
“…Lazar-Molnar et al 60 Barber et al 61 Fujita K et al 62 Sakai et al 63 Th1 cytokines and TB G Zeng et al Guerra-Laso et al 64 Che et al 65 Wareham et al 66 IL-7/15 ELISA, cytometric bead assay Enhanced Mtb survival was shown in IL-7-or IL-15-treated mice.…”
Section: Pd-1 Real-time Pcr Flow Cytometrymentioning
confidence: 99%
“…The involvement of IL-26 in host defense against intracellular bacteria has also been indicated [22] . A recent study described the potential role of IL-26 infection with Mycobacterium tuberculosis in isolated human blood monocytes cultured in vitro [22].…”
Section: Host Defensementioning
confidence: 99%
“…A recent study described the potential role of IL-26 infection with Mycobacterium tuberculosis in isolated human blood monocytes cultured in vitro [22]. By screening for altered gene expression with microarray analysis, it was discovered that the IL-26 gene was downregulated in monocytes from tuberculosis patients.…”
Section: Host Defensementioning
confidence: 99%
“…Given its expression by both hematopoietic and nonhematopoietic cells, and its role as a mediator of inflammation and protection against invading pathogens, the role of IL-26 at the lung mucosal surface is of great interest. Very little is known of IL-26 expression in the lungs, although one recent publication has shown an association between lower levels of IL-26 expression in serum of patients with tuberculosis (8). Interestingly, in monocytes infected with Mycobacterium tuberculosis, treatment with IL-26 inhibited M. tuberculosis killing, based on which IL-26 has been considered a "candidate gene for tuberculosis susceptibility" (8).…”
mentioning
confidence: 99%